A response to comment on prognostic factors in burns - Zieliński, Michał; Wróblewski, Piotr; Kozielski, Jerzy (Anestezjologia Intensywna Terapia, 2021)
We would like to thank Dr Ewington et al. for the commentary on our review about prognostic factors in burns. First we would like to comment on the role of frailty in assessment of burns. The elderly population is of special interest in all fields of clinical medicine, owing to the ageing of the world population [1]. The definition of frailty is relatively concise. It is defined as a state of depletion of the homeostatic reserve due to changes accumulated during lifetime. In consequence, resolution of stressor sequelae is impaired [2]. Although the definition is straightforward, the methods of its application and quantification of frailty are not unequivocally accepted [3]. Ward and Romanowski in their papers used the Clinical Frailty Scale [4]. Other developed scales, to mention only a few, are the general Korean Frailty Index for Primary Care [5], the Modified Frailty Index 5 (mFI-5) [6], the more specialized Emergency General Surgery Frailty Index [7], and the Burn Frailty Index [8]. Some of them were evaluated in surgery patients, and the Burn Frailty Index was developed by Maxwell specifically to be used in burn patients [8]. A study comparing the usefulness of various frailty scales in a burn ward would be a welcome addition to the discussion about burn outcomes. We would also like to address one more aspect of frailty. Generally, the term is connected with the elderly population, i.e. more than 65 years old. This is based on the fact that one’s frailty is a sum of deficits accumulated over the whole lifetime [9]. Yet even in younger age groups various tools used to assess frailty show a relatively high percentage of frail people [10, 11]. Research including patients undergoing orthopaedic surgery has proven that frailty assessment is a viable choice to predict complications even in younger groups [12]. Therefore we assume that frailty indexes will gradually become tools used also in younger groups of patients.